Black Boy, Black Boy - Kamanda, Ali; Redmond, Jorge; Daley, Ken, 1976- (Naperville, Illinois : Sourcebooks eXplore, 2022)
"Illustrations and rhyming text encourage Black boys to learn about the accomplishments of famous men in Black history and then forge their own paths"--
Keywords: African Americans -- Juvenile fiction; Self-confidence -- Juvenile fiction; African Americans -- Fiction; Self-confidence -- Fiction; Stories in rhyme; Picture books